2013
DOI: 10.1007/s10198-013-0534-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility of ranolazine for the symptomatic treatment of patients with chronic angina pectoris in Spain

Abstract: Ranolazine is a highly efficient add-on therapy for the symptomatic treatment of chronic angina pectoris in patients who are inadequately controlled by, or intolerant to, first-line antianginal therapies in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…A small number of prior European economic analyses performed from the Spanish, 20 Italian 21 and Russian perspectives 22 have also demonstrated the addition of ranolazine to SoC for the treatment of patients with chronic angina can be economically substantiated. Two of these analyses 20 21 reported ICERs for ranolazine of ∼€8500/QALY gained; well below the €30 000/QALY gained willingness-to-pay threshold commonly referenced. The third, a Russian model, 22 did not calculated cost/QALY gained but rather used change in angina frequency as its principal measure of effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of prior European economic analyses performed from the Spanish, 20 Italian 21 and Russian perspectives 22 have also demonstrated the addition of ranolazine to SoC for the treatment of patients with chronic angina can be economically substantiated. Two of these analyses 20 21 reported ICERs for ranolazine of ∼€8500/QALY gained; well below the €30 000/QALY gained willingness-to-pay threshold commonly referenced. The third, a Russian model, 22 did not calculated cost/QALY gained but rather used change in angina frequency as its principal measure of effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report of the cost-effectiveness of ranolazine from the UK health system perspective, and our findings are supportive of NICE's current recommendation for ranolazine use in stable angina. 8 Additionally, the aforementioned models 20–22 used only direct medical costs, while our model (as a sensitivity analysis) included both direct and indirect costs. The addition of indirect costs to our model yielded an even larger gap (decrease) in treatment costs with the use of ranolazine compared with SOC alone (δ: £488 vs £110), substantiating the benefit of ranolazine from a societal perspective.…”
Section: Discussionmentioning
confidence: 99%
“…A decision tree model [ 24 ] was locally adapted to evaluate the cost-utility of ranolazine as add-on therapy to SoC, compared to SoC alone, during a 6-month period (time horizon) in patients with stable angina, who did not respond adequately to first line therapy with b-blockers and/or calcium channel antagonists in Greece. The analysis was conducted from a third-party payer perspective (National Organization for Healthcare Services Provision [EOPYY]).…”
Section: Methodsmentioning
confidence: 99%
“…Recent pharmaco-economic studies conducted both in Europe and in the USA have shown ranolazine to be cost-effective in patients with chronic stable angina. A recent study from Spain calculated the incremental cost-utility ratio of using ranolazine compared with a placebo and showed that the incremental cost-utility ratio is 8,455 Euro per quality-adjusted life-year (QALY)/patient in Spain and that the incremental cost-utility ratio is particularly effective in non-hospitalized patients with mild or moderate angina frequency [ 26 ].…”
Section: Clinical Indication For the Use Of Ranolazine In Chronic Stamentioning
confidence: 99%